Menumbuhkan Minat Literasi melalui Mendongeng pada Kalangan Anak Usia Dini di TPA Tambun, Bekasi - Dhian Tyas Untari; Fata Nidaul Khasanah; Fina Zahra; Bianca Salikha Ramadhani; Siti Nur Khofifah (Universitas Teknologi Yogyakarta, 2024)
The main urgency of this activity is that low literacy is a complex problem and requires movement efforts as a form of attention to Indonesia. Therefore, Indonesia needs to implement the Sustainable Development Goals (SDGs) program with the aim of improving and advancing human welfare. The Al-Quran Education Park (TPA) is used as a partner in the implementation of community service. The selection of partners is due to several problems faced by partners in current conditions, including a) the lack of reading book materials as literacy media; b) There is no program that can be used as a medium to foster a literacy culture to realize sustainable quality education. The solution offered is in the form of procurement of reading books that are tailored to the needs of partners, the second solution is to create an activity program that can later foster a literacy culture in the partner environment through storytelling. As a result of the overall activities, partners felt the benefits of the proposed program and from the results of the percentage evaluation questionnaire that was achieved 100%.